Challenges of Heritage Conservation on a High-Density Island Port Hamlet Mitarai town, Hiroshima, Japan - Utaka, Yushi (International Planning History Society Proceedings, 2024)
Seto Inland Sea has been functioning maritime transportation and fishery since ancient age. The urban history of Mitarai town has well reflect development process of regional maritime transportation and entertainment sectors for transit passengers. The town is well remained and representing glory of regional maritime legacy and architectural heritages which known as the highest population density of the region. Since the diffusion of new transportation modes, the town faces serious social shrinkage which significantly appeared social ageing and depopulation. Recent hope in Mitarai town where included nation’s 36th preservation district in 1994, however, community faces significant social changes which endangered to sustain substance of local living culture. A number of issues are yet to be addressed to secure residents’ contemporary living needs, which includes: maintaining sustainable tourism demands; prevention measures for natural disasters; appropriate community engagements; and encourage local entrepreneurs. In this paper, author firstly collect and analyse the periodical development discourse on the Seto Inland Sea region, particularly historic transformation of the Mitarai town and the region. Secondly, to analyses development / preservation discourses in Mitarai town.